Multicentre Evaluation of IL Test™ Free PS: A Fully Automated Assay to Quantify Free Protein S - Serra, Josep; Sales, Miquel; Chitolie, Andrew; Domènech, Pere; Rossi, Edoardo; Borrell, Montserrat; Dahlbäck, Björn (Thrombosis and Haemostasis, 2002)
Deficiency of the anticoagulant vitamin K-dependent protein S (PS) is associated with increased risk of venous thrombosis. In human plasma, PS circulates in two forms: as free protein (free PS) and PS bound to C4b-binding protein (C4BP), a regulator of the complement system. Assays for free PS have higher sensitivity and specificity for protein S deficiency than assays for total protein S. We have extensively evaluated the analytical performance of a novel assay for free PS, the IL Test™ Free Protein S, which takes advantage of the affinity of C4BP for free PS, and compared its performance to existing methods. IL Test™ Free Protein S is a rapid, fully automated turbidimetric assay consisting of two reagents: a C4BP coated latex and an anti-PS monoclonal antibody coated latex. The test range, precision and linearity were adequate and the assay tolerated high concentrations of interfering substances of clinical significance. The reference range agreed with previously published studies. The analysis of 903 patient samples belonging to 20 different clinical categories with the new assay yielded free PS results that agreed well with those obtained using the assays established in the participating laboratories. The study demonstrated the IL Test™ Free Protein S to be rapid, reliable and easy to perform.
Keywords: Protein S; coagulation inhibitors; thrombosis; thrombophilia